Antiepileptic Drugs in the Neurosurgical Intensive Care - Varelas, Panayiotis N.; Jones, Mathew (Current Pharmaceutical Design, 2017)
The etiology of seizures in the Neurosurgical/Neurological Intensive Care Unit (NICU) can be categorized as emanating from either primary brain pathology, at either macro- or microscopic level, or from physiological derangements of critical care illness such as toxic or metabolic abnormalities. Particular etiologies at risk for seizures include ischemic or hemorrhagic stroke and traumatic brain injury. The use of prophylactic antiepileptic drug administration remains controversial in many situations, with most of the larger studies having used older antiepileptic drugs prophylactically. If seizures do occur, patients are typically treated with parenteral antiepileptic drugs. The duration of treatment is unknown in most situations, but it should be individualized depending on acute and monophasic injury versus chronic process. Late seizures, which occur after the first 2 weeks from the insult, have a more ominous risk for subsequent epilepsy and should be treated for extended periods of time or indefinitely. Electrolyte and glucose abnormalities and medications at high or low levels, when corrected, usually lead to seizure control. This review discusses the risk for seizures with commonly encountered types of brain injuries in the NICU and ends by examining the treatment algorithms for simple seizures and status epilepticus and the role newer antiepileptics may potentially play.
Keywords: trauma